Low magnesium intake is associated with increased knee pain in subjects with radiographic knee osteoarthritis: data from the Osteoarthritis Initiative. Issue 5 (May 2018) - Shmagel, A.; Onizuka, N.; Langsetmo, L.; Vo, T.; Foley, R.; Ensrud, K.; Valen, P.
Summary: Objective: As magnesium mediates bone and muscle metabolism, inflammation, and pain signaling, we aimed to evaluate whether magnesium intake is associated with knee pain and function in radiographic knee osteoarthritis (OA). Methods: We investigated the associations between knee pain/function metrics and magnesium intake from food and supplements in 2548 Osteoarthritis Initiative cohort participants with prevalent radiographic knee OA (Kellgren–Lawrence score ≥2). Magnesium intake was assessed by Food Frequency Questionnaire (FFQ) at baseline. WOMAC and Knee Injury and Osteoarthritis Outcome Score (KOOS) scores were reported annually with total follow up of 48 months. Analyses used linear mixed models. Results: Among participants with baseline radiographic knee OA the mean total magnesium intake was 309.9 mg/day (SD 132.6) for men, and 287.9 mg/day (SD 118.1) for women, with 68% of men and 44% of women below the estimated average requirement. Subjects with lower magnesium intake had worse knee OA pain and function scores, throughout the 48 months ( P < 0.001). After adjustment for age, sex, race, body mass index (BMI), calorie intake, fiber intake, pain medication use, physical activity, renal insufficiency, smoking, and alcohol use, lower magnesium intake remained associated with worse pain and function outcomes (1.4 points higher WOMAC and 1.5 points lower KOOS scores for every 50 mg of daily magnesium intake, P < 0.05). Fiber intake was an effect modifier ( P for interaction <0.05). The association between magnesium intake and knee pain and function scores was strongest among subjects with low fiber intake. Conclusion: Lower magnesium intake was associated with worse pain and function in knee OA, especially among individuals with low fiber intake.